2016
DOI: 10.1371/journal.pone.0156682
|View full text |Cite
|
Sign up to set email alerts
|

Wolf (Canis lupus) Generation Time and Proportion of Current Breeding Females by Age

Abstract: Information is sparse about aspects of female wolf (Canis lupus) breeding in the wild, including age of first reproduction, mean age of primiparity, generation time, and proportion of each age that breeds in any given year. We studied these subjects in 86 wolves (113 captures) in the Superior National Forest (SNF), Minnesota (MN), during 1972–2013 where wolves were legally protected for most of the period, and in 159 harvested wolves from throughout MN wolf range during 2012–2014. Breeding status of SNF wolves… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(33 citation statements)
references
References 31 publications
(48 reference statements)
0
33
0
Order By: Relevance
“…We carried out ancestry block analyses in Eurasian wolves in comparison with domestic dogs, applying a method implemented in the Lamp software that did not require the use of nonadmixed reference populations. Under the assumption of a recent admixture in the past 10 generations (corresponding to about 30–40 years; Mech & Seal, ; Mech, Barber‐Meyer, & Erb, ) we were able to detect first‐generation wolf–dog hybrids, recent back‐crosses, and assess the overall level of admixture. The results we obtained when comparing Eurasian wolves and dog breeds of diverse origin were highly consistent with the results for a reduced data set consisting of European wolves and European dog breeds only.…”
Section: Discussionmentioning
confidence: 99%
“…We carried out ancestry block analyses in Eurasian wolves in comparison with domestic dogs, applying a method implemented in the Lamp software that did not require the use of nonadmixed reference populations. Under the assumption of a recent admixture in the past 10 generations (corresponding to about 30–40 years; Mech & Seal, ; Mech, Barber‐Meyer, & Erb, ) we were able to detect first‐generation wolf–dog hybrids, recent back‐crosses, and assess the overall level of admixture. The results we obtained when comparing Eurasian wolves and dog breeds of diverse origin were highly consistent with the results for a reduced data set consisting of European wolves and European dog breeds only.…”
Section: Discussionmentioning
confidence: 99%
“…However, it has been suggested that the generation time of wolves is 4.2–5 years (e.g. Mech, Barber‐Meyer, & Erb, ; vonHoldt et al, ). Using 4.5 years as generation time increases the cited mutation rate estimates to an interval of 0.45–0.84 × 10 −8 .…”
Section: Methodsmentioning
confidence: 99%
“…3 years), and the grey wolf ( Canis lupis , c . 5 years), a species with which the thylacine shares many convergent affinities (Jones et al., ; Mech, Barber‐Meyer & Erb, ; Wroe, Clausen, McHenry, Moreno & Cunningham, ; Wroe & Milne, ).…”
Section: Methodsmentioning
confidence: 99%